Alternative comics : an emerging literature - Hatfield, Charles, 1965- (University Press of Mississippi, 2005)
In the 1980s, a sea change occurred in comics. Fueled by Art Spiegelman and Franoise Mouly's avant-garde anthology Raw and the launch of the Love Rockets series by Gilbert, Jaime, and Mario Hernandez, the decade saw a deluge of comics that were more autobiographical, emotionally realistic, and experimental than anything seen before. These alternative comics were not the scatological satires of the 1960s underground, nor were they brightly colored newspaper strips or superhero comic books. In Alternative Comics: An Emerging Literature, Charles Hatfield establishes the parameters of alternative comics by closely examining long-form comics, in particular the graphic novel. He argues that these are fundamentally a literary form and offers an extensive critical study of them both as a literary genre and as a cultural phenomenon. Combining sharp-eyed readings and illustrations from particular texts with a larger understanding of the comics as an art form, this book discusses the development of specific genres, such as autobiography and history.